Pengaruh Kecemasan Belajar dan Pemahaman Konsep Matematika Siswa terhadap Kemampuan Penalaran Matematika - Munasiah Munasiah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2015)
This research was conducted in order to know the influence of the anxiety of learning and students' understanding of mathematical concepts penanalaran mathematical abilities of students. The hypothesis of this study include: 1) There is a significant direct effect on the ability of anxiety learn mathematical reasoning. 2) There is significant direct influence students' understanding of mathematical concepts of mathematical reasoning abilities. 3) There is a significant direct effect of anxiety learn to understanding math concepts students. 4) There is a significant indirect effect on the ability of anxiety learn mathematical reasoning through the understanding of math concepts students. The method used in this research is survey method. Affordable population is class VIII students of academic year 2014/2015 a private SMP in Depok. A large sample of 80 students, with a sampling technique used was multistage sampling, taken four private schools. Research instrument used is questionnaire anxiety to learn as much as 25 statement, test understanding of mathematical concepts as much as 23 multiple choice questions, tests of mathematical reasoning ability in the form of an essay as much as 10 questions, which te; ah tested its validity. Analysis of data using path analysis. Hypothesis testing results show that: 1) There is a direct effect not significant anxiety study on the ability of mathematical reasoning, 2) There is a direct effect of significant understanding of the mathematical concept of the ability of mathematical reasoning, 3) There is a direct effect not significant anxiety learn to understanding of mathematical concepts , 4) There is the indirect effect which is not significant anxiety on the ability to learn mathematical reasoning. Keywords: anxiety of learning , mathematical concepts , mathematical reasoning